Statistical investigation of characteristic parameters for Au/p-TlInS2/n-InP pseudo Schottky junctions produced under the same conditions - Bahattin Abay; Dilek Aslancan; Nezaket Kulakac; Ayşe Nida Beştaş; Fatih Aktaş; Seda Yazıcı (Journal of Anatolian Physics and Astronomy)
Pseudo-Schottky junctions (PSJs) on moderately doped (MD) n-InP were fabricated by introducing a thin p-TlInS2 counter layer before the assembly of gold rectifying contact. Successively annealing treatment was applied to create a stable inversion layer at the metal-semiconductor (MS) interface. PSJs were made with a significant barrier height (BH) enhancement, typically by the value of 0.260 eV for gold Schottky gate, after the second annealing process at 200 oC in a nitrogen atmosphere for 5 minutes. Junction parameters such as BH, ideality factor (n) and serial resistance (Rs) of identically fabricated (18 dots) Au/p-TlInS2/n-InP PSJs have been computed by thermionic emission (TE) theory from current-voltage (I-V) and capacitance-voltage (C-V) characteristics, at room temperature and in the dark. BHs derived from I-V and C-V characteristics varied from 0.620 to 0.844 eV and 0.669 to 0.973 eV, respectively. In addition, the values of n varied from 1.023 to 1.706 and the serial resistances Rs varied from 28.3 to 131 Ω. Since all parameters of PSJs differ from one junction to another, even if they are prepared under the same conditions, a statistical study was made on the junction parameters using Tung’s model. The mean values of the experimental BH, the ideality factor, and the series resistance data, which were fitted by the Gaussian function, were found to be ϕ ̄_(I-V)=(0.7⁡5 5 〖±0.0〗⁡5 9) eV, ϕ ̄_(C-V)=(0.8⁡0 3 〖±0.〗⁡0 78) eV, n =(〖1.〗⁡3 84 〖±0.〗⁡1 52) and〖 R〗_s=(88.4 ±⁡2 8.0)Ω, respectively. The lateral homogeneous BH (ϕ_(hom.)) value of 0.800 eV for the Au/p-TlInS2/n-InP junctions has been obtained from the ϕ_(eff.) "- n" plot by using n_(imf.)=1.00⁡6 and Δϕ_(imf.)=18.0 meV It has been seen that the mean BH obtained from the C-V measurements correlates well with the value of ϕ_(hom.). The good agreement in these parameters indicates that the BH inhomogeneity observed in the Au/p-TlInS2/n-InP PJ can be described by considering the spatial distribution hypothesis of BH put forward by Tung.